Agri-WorldSources, an open online platform that integrates hydrological models and environmental data to inform design of water harvesting for agriculture - CGIAR Research Program on Water, Land and Ecosystems (2021)
This is an open online platform initially developed in Honduras but now being extended to support design of water harvesting for agriculture and domestic water. Started in Honduras and in 2021 was expanded to African countries.